2011
DOI: 10.1007/s10725-011-9612-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cytokinin levels and metabolism in tobacco (Nicotiana tabacum L.) explants during in vitro shoot organogenesis induced by trans-zeatin and dihydrozeatin

Abstract: The uptake and metabolism of trans-zeatin and/or dihydrozeatin, in correlation with cytokinin oxidase/ dehydrogenase (CKX) and b-glucosidase activity, were studied in leaf segments derived from wild-type (WT) and transgenic (T) tobacco (Nicotiana tabacum L. cv. Petit Havana SR1) during in vitro induction of shoot organogenesis. T explants harbored the maize gene Zm-p60.1 b-glucosidase. Higher levels of shoot regeneration were observed on T explants in the early stages of cultivation. In WT explants, the conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The increase in the total CK pool after exogenous CK treatment was due to increases in the abundance of different metabolites, which depended on the type of CK used, the concentration applied (Bairu et al ) and/or the culture stage being studied (Klemš et al ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The increase in the total CK pool after exogenous CK treatment was due to increases in the abundance of different metabolites, which depended on the type of CK used, the concentration applied (Bairu et al ) and/or the culture stage being studied (Klemš et al ).…”
Section: Discussionmentioning
confidence: 68%
“…The simultaneous occurrence of CK bases with the corresponding nucleosides and nucleotides in plant tissues suggests that the metabolic flow from CK nucleotides to the active bases is probably circular rather than unidirectional (Sakakibara ). Several authors have argued that the free bases are the physiologically active species, with the ribosides and ribotides being transport forms (Klemš et al ). In addition, CK glucosylation has been observed at the N3, N7 and N9 positions of the purine moiety (generating N ‐glucosides) and at the hydroxyl group of the side chain (generating O ‐glucosides).…”
Section: Introductionmentioning
confidence: 99%
“…Highest amount of bases, the active forms of cytokinins (Klemš et al, 2011), were found in Se developed under 18 and 23°C and low gellan gum concentration, treatments showing the highest water availability. So, our results are in agreement to other authors describing that a decrease in water availability could be related to the rapidly utilization of CK bases and tightly regulated by mechanisms that prevent their accumulation at high levels (Moncaleán et al, 2005; Stirk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This variation among genotypes might be related to the level of endogenous hormones [30] or the effect of exogenous growth regulators on the level of endogenous hormones through influencing their biosynthesis and distribution [31], which subsequently alters the in vitro regeneration responses [32][33][34]. Interestingly, all three improved tef varieties used in the current study had extremely poor regeneration capacity.…”
Section: Discussionmentioning
confidence: 83%